Comparison of Polyphenolic Content and Bioactivities Between Extracts from the Living Plants and Beach Deposits of the Submerged Brackish Water Angiosperm Ruppia maritima - Alkistis Kevrekidou; Nikolaos Goutzourelas; Stavroula Savvidi; Varvara Trachana; Andreana N. Assimopoulou; Ming Liu; Paraskevi Malea; Dimitrios Stagos (Molecules, 2025)
Bioactive extracts from living plants (LR) and beach deposits (NR) of the submerged brackish water angiosperm Ruppia maritima were examined for their antioxidant activity and anticancer potential. LR extract scavenged effectively free radicals with IC50 values of 38.00 μg/mL (DPPH•), 12.00 μg/mL (ABTS•+), 281.00 μg/mL (OH•), and 53.00 μg/mL (O2•), and exhibited reducing activity with an RP0.5AU value of 37.00 μg/mL. NR extract retained a significant part of LR extract’s antioxidant activity by scavenging free radicals with IC50 values of 180.00 μg/mL (DPPH•), 60.00 μg/mL (ABTS•+), and 164.00 μg/mL (O2•), and exhibited reducing activity with an RP0.5AU value of 107.00 μg/mL. Importantly, NR extract (IC50 value: 60.00 μg/mL) exhibited much higher inhibitory activity than LR extract (IC50 value: 1100.00 μg/mL) in XTT assay. HPLC analysis revealed that both R. maritima extracts contained phenolics, such as chicoric acid, quercetin-3-O-glucopyranoside, p-coumaric acid, 3,5-dimethoxy-4-hydroxicinnanic acid, trans-ferulic acid, and rutin hydrate, possessing antioxidant and/or anticancer activity. Thus, the present study showed for the first time that R. maritima extracts from either LR or NR are a promising source of bioactive compounds having beneficial properties for human health.